Пряма нейрорафія поворотного нерва як засіб корекції дисфонічних розладів за однобічних паралічів голосових складок - Паламарчук, В. О. (Clinical Endocrinology and Endocrine Surgery, 2012)
The paper presents the results of laryngeal reinnervation for unilateral vocal cord paralysis that result from operations on the thyroid gland. Reinnervation was performed by direct neurorrhaphy recurrent laryngeal nerve (RLN). A total of 29 people, 15 of which were the main group and 14 – control. The main group consisted of eight patients who had RLN – RLN neurorrhaphy was done during the primary surgery on the thyroid gland is damaged RLN IV – Vst. by J. Sunderland and 7 patients neurorrhaphy RLN – RLN was made after repeated operations on the thyroid gland. The control group of 14 people receiving traditional therapy. The objective examination included videolarigoskopiyu, the study of spectral analysis of voice, maximum phonation time. Subjective – VHI – questioning. The survey was conducted prior to surgery in the early postoperative period, after 6 months and 1 year after surgery. In the study group is not marked recovery of functional mobility of the vocal folds, but the recorded indirect signs of reinnervation – toning mm vocalis et thyroarythenoideus, the clinical equivalent of which is improved almost to normal values of objective and subjective indicators of voice (harmonic- to- noise ratio, maximum phonation time, VHI-index). In three cases noted the development of the larynx synkineses without compromising respiratory functions. In the control group, significant improvement in the studied parameters were recorded.